I survived : the attack of the grizzlies, 1967 - Ball, Georgia; Ball, Georgia (I survived (Graphic novel series), 2022)
Presents a graphic novel detailing eleven-year-old Melody Vega and her family's visit to Glacier National Park for their annual trip in 1967. Melody has a frightening encounter with a grizzly bear, making her a part of one of the deadliest seasons in the history of America's national parks. Includes an author's note, information about grizzlies, tips for encountering a grizzly bear, and advice for protecting the wilderness and its wildlife.